(Meth) Acrylic Resin Film, Adhesive Sheet, And Polarizing Film
By adopting a laminated (meth)acrylic resin film and using specific crosslinking agents and antioxidants, the problems of thinning and insufficient solvent resistance of PMMA resin film are solved, and high fit and fold resistance are achieved. Suitable for optical and display fields.
Patent Information
- Application Number
- CN202410826328.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-06-25
- Publication Date
- 2024-12-31
AI Technical Summary
In the process of thinning, the conventional PMMA resin film is difficult to reach a thickness of less than 40 μm, and in the solution casting method, the solvent resistance of the PMMA resin composition is insufficient, resulting in low operability.
The (meth)acrylic resin film with a laminated structure consists of a first resin layer and a second resin layer. The first resin layer contains a specific crosslinking agent and an antioxidant, and the second resin layer contains an isocyanate compound crosslinking agent. Preparation by solution casting method improves the firmness and solvent resistance of the resin layer.
It is realized that the fold resistance, shear resistance, extension resistance and solvent resistance of the (meth)acrylic resin film is improved while maintaining optical characteristics, and the clinging ability to the adherend is enhanced, which is suitable for optical applications and Display field.
Smart Images

Figure CN119217816A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a (meth) acrylic resin film, an adhesive sheet and a polarizing film. Background Art
[0002] In the past, from the excellent viewpoint of high transparency, heat processability, weatherability, chemical resistance, in the resin film for covering the various equipment parts surfaces such as electronic equipment, household electrical products, automobile interior and exterior parts, building components, use (methyl) acrylic resin (PMMA resin).In addition, in recent years, from the excellent viewpoints such as high transparency, weatherability, PMMA resin film is used as optical film.In the past, as the method for making PMMA resin film, from the viewpoint that makes productivity high, adopt the method that PMMA resin is utilized melt extrusion method to carry out film making.
[0003] For example, Patent Document 1 discloses a coating-substituting acrylic resin film suitable for use in a member integrated with a molding resin, particularly suitable for forming a surface protective layer. In Patent Document 1, a UV absorber and a lubricant added to the acrylic resin film are combined in specific types and proportions.
[0004] Patent Document 2 discloses a method for improving the impact resistance of an acrylic resin by excluding a rubber-containing graft copolymer that impairs the color tone and transparency of the acrylic resin. Patent Document 2 uses an acrylic resin composition containing a specific graft copolymer.
[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-286960
[0006] Patent Document 2: International Publication No. 2016 / 139927 Summary of the invention
[0007] The acrylic resin film of the invention described in Patent Document 1 is a resin film obtained by melt extrusion, and therefore has a problem that it is difficult to obtain a thin resin film with a film thickness of 40 μm or less. The acrylic resin composition of the invention described in Patent Document 2 is a process for obtaining a graft copolymer by gradually progressing and completing the graft polymerization reaction in 3 to 4 stages, and therefore has a problem that the process for obtaining the graft copolymer requires a long time.
[0008] Under these circumstances, a method for forming a film of PMMA resin by a solution casting method having the advantage of being able to form a thin film is required, and this method is a method for forming a resin film more convenient than a melt extrusion method. Furthermore, in optical applications and display applications using PMMA resin, the demand for thin film formation is increasing, and it is becoming a field where film formation by a melt extrusion method is not possible.
[0009] On the other hand, when a PMMA resin film is prepared by a solution casting method, it can be thinned to a thickness of less than 40 μm, but there is a problem that it is difficult to improve the performance of solvent resistance as a physical property of the obtained PMMA resin film. In the solution casting method, it is necessary to make the weight average molecular weight of the uncrosslinked PMMA resin used in the PMMA resin composition a large value of more than 1,000,000, so there is a problem that the solution of the PMMA resin composition is high in viscosity and the operability in the film-making process is low.
[0010] An object of the present invention is to provide a (meth)acrylic resin film, a pressure-sensitive adhesive sheet, and a polarizing film that improve the adhesion to an adherend while maintaining optical properties by using a (meth)acrylic resin composition having excellent folding resistance, cut resistance, elongation, and solvent resistance.
[0011] A first embodiment of the present invention is a (meth)acrylic resin film, comprising a first resin layer and a second resin layer stacked together, wherein the first resin layer is formed by cross-linking a first (meth)acrylic resin composition containing (A) a first (meth)acrylic polymer, a rubber compound, (A-3) a first cross-linking agent, and (A-4) a first antioxidant, and the second resin layer is formed by cross-linking a second (meth)acrylic resin composition containing (B) a second (meth)acrylic polymer, (B-3) a second cross-linking agent, and (B-4) a second antioxidant, and serves as an adhesion-enhancing resin layer of the first resin layer, wherein the first resin layer (A) is formed by cross-linking a second (meth)acrylic resin composition containing (B) a second (meth)acrylic polymer, (B-3) a second cross-linking agent, and (B-4) a second antioxidant. The (meth)acrylic polymer comprises a copolymer having a weight average molecular weight of more than 100,000 and less than 1,000,000 obtained by copolymerizing (A-1) a first (meth)acrylic acid alkyl ester and (A-2) a first copolymerizable monomer, wherein the first (meth)acrylic acid alkyl ester (A-1) comprises 80 parts by weight or more of methyl methacrylate and 100 parts by weight of at least one (meth)acrylic acid alkyl ester other than the methyl methacrylate, the homopolymer Tg of which is 0° C. or more and the carbon number of the alkyl group is C1 to C14, and the first (A-2) copolymerizable monomer comprises at least one copolymerizable monomer having a functional group capable of reacting with the first crosslinking agent (A-3). The total amount of the rubber compound is 1.0 to 20.0 parts by weight, the content of the rubber compound is 1.0 to 25.0 parts by weight relative to 100 parts by weight of the total amount of the first (meth)acrylic acid alkyl ester (A-1), the second (meth)acrylic polymer (B) comprises a copolymer having a weight average molecular weight of more than 100,000 and less than 1,000,000 obtained by copolymerizing the second (meth)acrylic acid alkyl ester (B-1) and the second copolymerizable monomer (B-2), and in the second (meth)acrylic acid alkyl ester (B-1), 80 parts by weight or more of methyl methacrylate and a homopolymer other than the methyl methacrylate have a Tg of less than 0°C and an alkyl group having a carbon number of C2 The total amount of at least one type of (meth)acrylic acid alkyl ester having a molecular weight of C10 to C18 is 100 parts by weight, the total amount of at least one type of copolymerizable monomer containing no carboxyl group and containing hydroxyl group in the (B-2) second copolymerizable monomer is 5 parts by weight to 30 parts by weight, the (B-3) second crosslinking agent is a difunctional or higher functional isocyanate compound, the content of the (B-3) second crosslinking agent is 1 part by weight to 5 parts by weight relative to the total amount of 100 parts by weight of the (B-1) second (meth)acrylic acid alkyl ester, the thickness of the first resin layer is 10 μm or less, the thickness of the second resin layer is 5 μm or less, and the haze value of the (meth)acrylic resin film is 1.0% or less.
[0012] A second embodiment is a (meth)acrylic resin film according to the first embodiment, wherein the (A-2) first copolymerizable monomer is one or more monomers selected from a monomer group consisting of a copolymerizable monomer containing a hydroxyl group and a copolymerizable monomer containing a carboxyl group, the (A-3) first crosslinking agent is one or more monomers selected from a compound group consisting of an epoxy compound, an aziridine compound and an isocyanate compound, and the content of the (A-3) first crosslinking agent is 0.1 to 5 parts by weight relative to a total of 100 parts by weight of the (A-1) first (meth)acrylic acid alkyl ester, and the (A-4) first antioxidant is one or more selected from a phenolic antioxidant, a thioether antioxidant, a phosphite antioxidant and a hindered amine antioxidant, and the content of the (A-4) first antioxidant is 0.01 to 0.5 parts by weight relative to a total of 100 parts by weight of the (A-1) first (meth)acrylic acid alkyl ester.
[0013] The third scheme is: a (meth) acrylic resin film according to the first scheme or the second scheme, wherein the rubber compound is a core-shell particle formed by a rubber layer with SBR or butadiene as the core part and an acrylic layer with methyl methacrylate as the main component as the shell part, and the volume-based average particle size of the core-shell particle is 0.1μm to 0.3μm.
[0014] The fourth embodiment is: a (meth) acrylic resin film according to any one of the first to third embodiments, wherein the (A-2) first copolymerizable monomer is a copolymerizable monomer containing a hydroxyl group, and the copolymerizable monomer containing a hydroxyl group is one or more selected from 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl methacrylate, 4-hydroxybutyl methacrylate, and 2-hydroxyethyl methacrylate.
[0015] The fifth embodiment is: a (meth) acrylic resin film according to any one of the first to fourth embodiments, wherein the (B-4) second antioxidant is one or more selected from phenolic antioxidants, thioether antioxidants, phosphite antioxidants, and hindered amine antioxidants, and the content of the (B-4) second antioxidant is 0.01 to 0.5 parts by weight relative to a total of 100 parts by weight of the (B-1) second (meth) alkyl ester.
[0016] The sixth embodiment is: a (meth) acrylic resin film according to any one of the first to fifth embodiments, wherein the (B-2) second copolymerizable monomer is a copolymerizable monomer containing a hydroxyl group, and the copolymerizable monomer containing a hydroxyl group is one or more selected from 8-hydroxyoctyl acrylate, 6-hydroxyhexyl acrylate, 4-hydroxybutyl acrylate, and 2-hydroxyethyl acrylate.
[0017] A seventh embodiment is the (meth)acrylic resin film according to any one of the first to sixth embodiments, wherein the thickness of the first resin layer is 0.1 μm to 9 μm, and the thickness of the second resin layer is 0.1 μm to 5 μm.
[0018] An eighth aspect is the (meth)acrylic resin film according to any one of the first to seventh aspects, wherein the (meth)acrylic resin film has an in-plane retardation Re of 1.0 nm or less.
[0019] A ninth embodiment is a (meth) acrylic resin film according to any one of the first to eighth embodiments, wherein the (meth) acrylic resin film has a gel fraction of 90% or more as solvent resistance, a folding endurance of 200 times or more as folding endurance measured in accordance with JIS P8115, and an elongation at break of 20% or more as elongation.
[0020] The tenth embodiment is: a (meth) acrylic resin film according to any one of the first to ninth embodiments, wherein, in a cellophane tape adhesion test in which the (meth) acrylic resin film is bonded to one side of a polarizer with a PVA adhesive and then a cellophane tape is bonded to the surface of the (meth) acrylic resin film and then peeled off, the (meth) acrylic resin film is not peeled off and only the cellophane tape is peeled off.
[0021] An eleventh aspect is a pressure-sensitive adhesive sheet comprising a (meth)acrylic resin film according to any one of the first to tenth aspects and a pressure-sensitive adhesive layer formed on one or both surfaces thereof.
[0022] A twelfth aspect is a polarizing film, wherein the (meth) acrylic resin film according to any one of the first to tenth aspects is formed on one or both sides of a polarizer, wherein the total thickness of the polarizing film is 80 μm or less.
[0023] According to the present invention, a (meth)acrylic resin film, a pressure-sensitive adhesive sheet, and a polarizing film can be provided which use a (meth)acrylic resin composition having excellent folding resistance, cut resistance, elongation, and solvent resistance and improves adhesion to an adherend while maintaining optical properties.
[0024] The first resin layer contains a first (meth) acrylic polymer composed of a copolymer obtained by copolymerizing specific monomers at a specific ratio, a rubber compound, and a first antioxidant, thereby obtaining a (meth) acrylic resin film having excellent folding resistance, cut resistance, elongation, and solvent resistance, and particularly significantly improved folding resistance and elongation. The second resin layer is laminated on the first resin layer as an adhesion-improving resin layer, thereby improving adhesion to the adherend. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a cross-sectional view showing an example of the (meth)acrylic resin film according to the embodiment.
[0026] Figure 2 This is a cross-sectional view showing an example of a pressure-sensitive adhesive sheet according to an embodiment.
[0027] Figure 3 This is a cross-sectional view showing an example of a polarizing film according to an embodiment.
[0028] (Explanation of Reference Numerals)
[0029] 10: (Meth) acrylic resin film
[0030] 11: First resin layer
[0031] 12: Second resin layer
[0032] 20: Adhesive sheet
[0033] 21: Adhesive layer
[0034] 30: Polarizing film
[0035] 31: Polarizer DETAILED DESCRIPTION
[0036] Hereinafter, the present invention will be described based on suitable embodiments. Figure 1 As shown, the (meth)acrylic resin film of the embodiment is a (meth)acrylic resin film 10 in which a first resin layer 11 and a second resin layer 12 serving as an adhesion-enhancing resin layer of the first resin layer 11 are laminated.
[0037] The first resin layer 11 is formed by crosslinking a first (meth) acrylic resin composition containing (A) a first (meth) acrylic polymer, a rubber compound, (A-3) a first crosslinking agent, and (A-4) a first antioxidant. The second resin layer 12 is formed by crosslinking a second (meth) acrylic resin composition containing (B) a second (meth) acrylic polymer, (B-3) a second crosslinking agent, and (B-4) a second antioxidant. The thickness of the first resin layer 11 is 10 μm or less, and the thickness of the second resin layer 12 is 5 μm or less. The haze value of the (meth) acrylic resin film 10 is 1.0% or less.
[0038] In the present specification, the (meth)acrylate may be any one of acrylate and / or methacrylate, or both may be used in combination.
[0039] <First (meth)acrylic resin composition>
[0040] The first (meth)acrylic resin composition is used to form the first resin layer 11. The content of the rubber compound contained in the first resin layer 11 is 1.0 to 25.0 parts by weight based on 100 parts by weight of the total of the (A-1) first alkyl (meth)acrylate.
[0041] The (A) first (meth)acrylic polymer comprises a copolymer having a weight average molecular weight of more than 100,000 and less than 1,000,000 obtained by copolymerizing (A-1) a first (meth)acrylic acid alkyl ester and (A-2) a first copolymerizable monomer, wherein the first (meth)acrylic acid alkyl ester (A-1) comprises 80 parts by weight or more of methyl methacrylate and 100 parts by weight of at least one (meth)acrylic acid alkyl ester other than the methyl methacrylate whose homopolymer has a Tg of 0° C. or more and an alkyl group having carbon atoms of C1 to C14, and the first (A-2) copolymerizable monomer comprises 1.0 to 20.0 parts by weight of at least one copolymerizable monomer having a functional group capable of reacting with the first crosslinking agent (A-3).
[0042] The first (meth)acrylic polymer (A) includes a copolymer obtained by copolymerizing the first (meth)acrylic acid alkyl ester (A-1) and the first copolymerizable monomer (A-2). The first (meth)acrylic polymer (A) may be a copolymer consisting of only the first (meth)acrylic acid alkyl ester (A-1) and the first copolymerizable monomer (A-2), or may be a copolymer further including a monomer other than these.
[0043] The alkyl group of the first (meth)acrylic acid alkyl ester (A-1) may be acyclic (linear, branched) or cyclic. In the following description, 100 parts by weight of the first (meth)acrylic acid alkyl ester (A-1) may be referred to as "100 parts by weight of (A-1)".
[0044] The first (meth)acrylic acid alkyl ester (A-1) contains 80 parts by weight or more of methyl methacrylate (A-1a) relative to a total of 100 parts by weight of (A-1). The content of (A-1a) may be a range having two ends selected from 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, and 99 parts by weight.
[0045] In addition to (A-1a) methyl methacrylate, (A-1) the first alkyl (meth)acrylate further comprises one or more alkyl (meth)acrylates (A-1b) other than (A-1a) whose homopolymer Tg is 0°C or higher and whose alkyl group has C1 to C14 carbon atoms.
[0046] Specific examples of (A-1b) include one or more selected from the group consisting of methyl acrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl (meth)acrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, and cyclohexyl (meth)acrylate.
[0047] The first (meth)acrylic acid alkyl ester (A-1) contains 20 parts by weight or less of the monomer belonging to (A-1b) relative to a total of 100 parts by weight of (A-1). The content of (A-1b) may be a range having two ends selected from any two points selected from 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, and 20 parts by weight. The first (meth)acrylic acid alkyl ester (A-1) may contain only (A-1a) and (A-1b), or may further contain other (meth)acrylic acid alkyl esters.
[0048] The first copolymerizable monomer (A-2) is one or more copolymerizable monomers having a functional group capable of reacting with the first crosslinking agent (A-3). The first copolymerizable monomer (A-2) is preferably one or more selected from the group consisting of copolymerizable monomers containing a hydroxyl group and copolymerizable monomers containing a carboxyl group.
[0049] As the first copolymerizable monomer (A-2), a copolymerizable monomer containing a hydroxyl group (a monomer not containing a carboxyl group) is preferred, and examples thereof include hydroxyl-containing (meth)acrylates such as hydroxyalkyl (meth)acrylates, etc. As specific examples thereof, one or more selected from 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl methacrylate, 4-hydroxybutyl methacrylate, and 2-hydroxyethyl methacrylate can be mentioned.
[0050] The content of the first copolymerizable monomer (A-2) is preferably 1.0 to 20.0 parts by weight relative to 100 parts by weight of the total of (A-1). The content of the first copolymerizable monomer (A-2) may be a range having two ends selected from 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, and 20 parts by weight.
[0051] The method for producing the (A) first (meth)acrylic polymer is not particularly limited, but a suitable known polymerization method such as a solution polymerization method and an emulsion polymerization method can be used. The weight average molecular weight of the (A) first (meth)acrylic polymer is preferably greater than 100,000 and less than 1,000,000, more preferably greater than 100,000 and less than 950,000, and particularly preferably greater than 100,000 and less than 900,000. If the weight average molecular weight of the (A) first (meth)acrylic polymer is less than 100,000, even if the first (meth)acrylic resin composition is cross-linked, it is not easy to obtain the first resin layer 11 having excellent physical properties. If the weight average molecular weight of the (A) first (meth)acrylic polymer is greater than 1,000,000, the solution becomes highly viscous, and the operability of the film-forming process is poor.
[0052] The first (meth) acrylic resin composition used in the first resin layer 11 contains a rubber compound. The content of the rubber compound is preferably 1.0 to 25.0 parts by weight relative to a total of 100 parts by weight of (A-1). The content of the rubber compound may be a range having two ends selected from 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, and 25 parts by weight.
[0053] The rubber compound is not particularly limited as long as it is a polymer showing rubber-like elasticity, but a rubber compound having excellent dispersibility or miscibility with the (meth)acrylic polymer is preferred. For example, a rubber compound containing a vinyl polymer such as olefin elastomer, styrene elastomer, acrylic elastomer, acrylic rubber, nitrile rubber, butadiene rubber, polyisoprene rubber, and natural rubber is preferred.
[0054] The rubber compound is preferably a core-shell particle formed by a rubber layer of a core part and an acrylic layer of a shell part. As a specific example of the rubber compound, there can be cited core-shell particles formed by a rubber layer with styrene-butadiene rubber (SBR) or butadiene as a core part and an acrylic layer with methyl methacrylate as a shell part. The volume-based average particle size of the core-shell particle is preferably 0.1 μm to 0.3 μm.
[0055] As the first crosslinking agent (A-3), a compound having a crosslinkable functional group capable of undergoing a crosslinking reaction with the functional group possessed by the first (meth)acrylic polymer (A) can be cited. As a specific example of (A-3), one or more selected from the group consisting of epoxy compounds, aziridine compounds, and isocyanate compounds can be cited. The content of the first crosslinking agent (A-3) is preferably 0.1 to 5 parts by weight relative to a total of 100 parts by weight of (A-1).
[0056] The crosslinking agent composed of an epoxy compound (epoxy crosslinking agent) is not particularly limited as long as it is an epoxy compound with two or more functional groups, and examples thereof include one or more selected from the group consisting of polyglycidyl ethers of polyols (including diols, glycols, and bisphenols), diglycidyl esters of dicarboxylic acids, diglycidyl-substituted amines, tetraglycidyl-substituted diamines, and the like.
[0057] The crosslinking agent composed of an aziridine compound (aziridine crosslinking agent) is not particularly limited as long as it is an aziridine compound having two or more functional groups, a compound having two or more aziridine functional groups in one molecule, or the like. Examples of the aziridine functional group include 1-aziridinyl [-N(CH 2 ) 2 ], 2-aziridine group, substituted aziridine group having a substituent such as methyl group, and the like.
[0058] Examples of the crosslinking agent composed of an isocyanate compound (isocyanate crosslinking agent) include bifunctional isocyanates (diisocyanate compounds) such as aliphatic diisocyanates and aromatic diisocyanates; and trifunctional or higher-functional polyisocyanate compounds such as their biuret-modified products, isocyanurate-modified products, and adducts.
[0059] The first antioxidant (A-4) is not particularly limited and can be appropriately selected from known antioxidants. Specific examples of the first antioxidant (A-4) include one or more selected from phenolic antioxidants, thioether antioxidants, phosphite antioxidants, and hindered amine antioxidants. The content of the first antioxidant (A-4) is preferably 0.01 to 0.5 parts by weight relative to a total of 100 parts by weight of (A-1).
[0060] The first (meth) acrylic resin composition is not limited to the above-mentioned additives, and may be appropriately blended with known additives such as surfactants, curing accelerators, curing retardants, plasticizers, fillers, lubricants, processing aids, anti-aging agents, heat stabilizers, light stabilizers, antistatic agents, colorants, ultraviolet absorbers, infrared absorbers, etc. These additives may be used alone or in combination of two or more.
[0061] <Second (meth)acrylic resin composition>
[0062] The second (meth)acrylic resin composition is used to form the second resin layer 12. The second crosslinking agent (B-3) is a difunctional or higher functional isocyanate compound and is contained in an amount of 1 to 5 parts by weight based on a total of 100 parts by weight of the second (meth)acrylic acid alkyl ester (B-1).
[0063] The (B) second (meth)acrylic polymer comprises a copolymer having a weight average molecular weight of more than 100,000 and less than 1,000,000, which is obtained by copolymerizing (B-1) a second (meth)acrylic acid alkyl ester and (B-2) a second copolymerizable monomer, wherein the second (meth)acrylic acid alkyl ester (B-1) comprises 80 parts by weight or more of methyl methacrylate and 100 parts by weight of at least one (meth)acrylic acid alkyl ester other than the methyl methacrylate whose homopolymer has a Tg of less than 0°C and an alkyl group having carbon atoms of C2 to C18, and the second (B-2) copolymerizable monomer comprises 5 to 30 parts by weight of at least one copolymerizable monomer having no carboxyl group and containing a hydroxyl group.
[0064] The (B) second (meth)acrylic polymer includes a copolymer obtained by copolymerizing the (B-1) second (meth)acrylic acid alkyl ester and the (B-2) second copolymerizable monomer. The (B) second (meth)acrylic polymer may be a copolymer consisting of only the (B-1) second (meth)acrylic acid alkyl ester and the (B-2) second copolymerizable monomer, or may be a copolymer further including a monomer other than these.
[0065] The alkyl group of the second (meth)acrylic acid alkyl ester (B-1) may be acyclic (linear, branched) or cyclic. In the following description, 100 parts by weight of the second (meth)acrylic acid alkyl ester (B-1) may be referred to as "100 parts by weight of (B-1)".
[0066] The second (meth)acrylic acid alkyl ester (B-1) contains 80 parts by weight or more of methyl methacrylate (B-1a) relative to a total of 100 parts by weight of (B-1). The content of (B-1a) may be a range having two ends selected from 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, and 99 parts by weight.
[0067] The second alkyl (meth)acrylate (B-1) contains, in addition to methyl methacrylate (B-1a), one or more alkyl (meth)acrylates (B-1b) other than (B-1a) whose homopolymer Tg is 0°C or lower and whose alkyl group has carbon atoms of C2 to C18.
[0068] Specific examples of (B-1b) include one or more selected from the group consisting of ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, isohexyl acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, and lauryl (meth)acrylate.
[0069] The second (meth)acrylic acid alkyl ester (B-1) contains 20 parts by weight or less of the monomer belonging to (B-1b) relative to a total of 100 parts by weight of (B-1). The content of (B-1b) may be a range having two ends selected from any two points selected from 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, and 20 parts by weight. The second (meth)acrylic acid alkyl ester (B-1) may contain only (B-1a) and (B-1b), or may further contain other (meth)acrylic acid alkyl esters.
[0070] (B-2) The second copolymerizable monomer is a copolymerizable monomer containing no carboxyl group and a hydroxyl group, and examples thereof include hydroxyl-containing (meth)acrylates such as hydroxyalkyl (meth)acrylates, etc. Specific examples thereof include one or more selected from 8-hydroxyoctyl acrylate, 6-hydroxyhexyl acrylate, 4-hydroxybutyl acrylate, and 2-hydroxyethyl acrylate.
[0071] The content of the second copolymerizable monomer (B-2) is preferably 5 to 30 parts by weight relative to a total of 100 parts by weight of (B-1). The content of the second copolymerizable monomer (B-2) may be a range having two ends selected from 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, and 30 parts by weight.
[0072] The method for producing the second (meth)acrylic polymer (B) is not particularly limited, and a suitable known polymerization method such as a solution polymerization method and an emulsion polymerization method can be used. The weight average molecular weight of the second (meth)acrylic polymer (B) is preferably greater than 100,000 and less than 1,000,000, more preferably greater than 100,000 and less than 950,000, and particularly preferably greater than 100,000 and less than 900,000. If the weight average molecular weight of the second (meth)acrylic polymer (B) is less than 100,000, even if the second (meth)acrylic resin composition is cross-linked, it is not easy to obtain the second resin layer 12 having excellent physical properties. If the weight average molecular weight of the second (meth)acrylic polymer (B) is greater than 1,000,000, the solution becomes highly viscous, and the operability of the film-forming process is poor.
[0073] The second crosslinking agent (B-3) is a difunctional or higher-functional isocyanate compound. The second crosslinking agent (B-3) can undergo a crosslinking reaction with the hydroxyl group of the second copolymerizable monomer (B-2) contained in the second (meth)acrylic polymer (B). The content of the second crosslinking agent (B-3) is preferably 1 to 5 parts by weight relative to a total of 100 parts by weight of (B-1).
[0074] Examples of difunctional or higher-functional isocyanate compounds include difunctional isocyanates (diisocyanate compounds) such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), and xylylene diisocyanate (XDI); and trifunctional or higher-functional polyisocyanate compounds such as their biuret-modified products, isocyanurate-modified products, and adducts. Examples of adducts include adducts of diisocyanate compounds with trivalent or higher-valent polyols such as trimethylolpropane (TMP) and glycerol.
[0075] The bifunctional isocyanate compound may be a compound obtained by reacting a diisocyanate compound such as TDI, XDI, MDI, HDI, IPDI, etc. with a diol compound. Examples of the diol compound include one or more selected from the group consisting of 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 2,2-dimethyl-1,3-propanediol monohydroxypivalate, polyethylene glycol (PEG), and polypropylene glycol.
[0076] The second antioxidant (B-4) is not particularly limited and can be appropriately selected from known antioxidants. Specific examples of (B-4) include one or more selected from phenolic antioxidants, thioether antioxidants, phosphite antioxidants, and hindered amine antioxidants. The content of the second antioxidant (B-4) is preferably 0.01 to 0.5 parts by weight relative to a total of 100 parts by weight of (B-1).
[0077] The second (meth) acrylic resin composition is not limited to the above-mentioned additives, and may be appropriately formulated with surfactants, curing accelerators, curing retardants, plasticizers, fillers, lubricants, processing aids, anti-aging agents, heat stabilizers, light stabilizers, antistatic agents, colorants, ultraviolet absorbers, infrared absorbers and other known additives. These additives may be used alone or in combination of two or more. The second (meth) acrylic resin composition preferably does not contain a rubber compound.
[0078] <(Meth)acrylic resin film>
[0079] The (meth)acrylic resin film 10 of the embodiment is a first resin layer 11 formed by crosslinking the first (meth)acrylic resin composition and a second resin layer 12 formed by crosslinking a second (meth)acrylic resin composition is laminated. The second resin layer 12 is an adhesion-enhancing resin layer of the first resin layer 11.
[0080] The thickness of the first resin layer 11 is preferably 10 μm or less, more preferably 0.1 μm to 9 μm. The thickness of the second resin layer 12 is preferably 5 μm or less, more preferably 0.1 μm to 5 μm. The second resin layer 12 may be thinner than the first resin layer 11 .
[0081] The first resin layer 11 and the second resin layer 12 can be formed using a solution casting method. Specifically, the following method can be used: after a solution of a (meth)acrylic resin composition is applied to a predetermined substrate to form a thin film, the thin film is heated and dried to volatilize the solvent from the thin film and cross-link the thin film at the same time. The second resin layer 12 can be stacked on the first resin layer 11, or the first resin layer 11 can be stacked on the second resin layer 12.
[0082] The substrate used in the solution casting method is not limited to a fixed plane, and examples thereof include a resin film unwound from a resin film roll, a movable belt, a drum, etc. The surface of the substrate is preferably a smooth surface, but the substrate may be provided with predetermined concavities and convexities to transfer the concavities and convexities to the surface of the obtained resin layer.
[0083] The (meth) acrylic resin film 10 obtained by the solution casting method can be stretched in a predetermined direction such as the length direction and the width direction, or can be kept in an unstretched state. When it is necessary to reduce the anisotropy in the use of the optical film, it is preferred to make the (meth) acrylic resin film 10 into a non-stretched film. In addition to the operation of stretching the (meth) acrylic resin film 10 in the length direction and the width direction, it can also be processed into a biaxially stretched film. It should be noted that the anisotropy of the film is not limited to the anisotropy of mechanical properties such as "elongation at break", and optical anisotropy such as "birefringence" can also be listed.
[0084] The mechanical properties of the (meth)acrylic resin film 10 also depend on the application, but it is preferred that the film has a large number of folding resistance as a folding resistance and a high tensile strength as a cut resistance, and also has a moderate elongation at break as an extensibility. For example, when the film is transported in the longitudinal direction, unwound from a roll, or wound on a roll, it is preferred that the elongation at break is not too small so as to obtain good conformability to an adherend, etc.
[0085] The number of folding resistance of the (meth)acrylic resin film 10 as measured according to JIS P8115 is preferably 200 times or more. As a common measurement condition of the number of folding resistance, the following method can be cited: a test piece with a width of 15.0±0.1 mm and a length of about 110 mm is repeatedly reciprocated and bent at a speed of 175±10 times per minute under a load of 9.8 N. The number of reciprocating bends until the test piece breaks is measured as the number of folding resistance.
[0086] The elongation at break of the (meth)acrylic resin film 10 as extensibility is preferably 20% or more. The elongation at break of films can be measured in accordance with standards such as JIS K7161 (Plastics - Determination of tensile properties) and JIS K7127 (Plastics - Test methods for tensile properties).
[0087] The gel fraction, which is solvent resistance, of the (meth)acrylic resin film 10 is preferably 90% or more. By increasing the gel fraction, solvent resistance, which is a physical property required of the (meth)acrylic resin film 10, can be improved.
[0088] The (meth) acrylic resin film 10 can be used as a substrate for an optical film. Examples of the optical film include polarizing films, phase difference films, anti-reflection films, anti-glare films, ultraviolet absorption films, infrared absorption films, optical compensation films, and brightness enhancement films. Examples of devices to which optical components are applied include liquid crystal panels, organic EL panels, and touch panels. When the (meth) acrylic resin film 10 is used as an optical film, it is preferably colorless and transparent.
[0089] The in-plane phase difference Re of the (meth)acrylic resin film 10 is preferably 1.0 nm or less. The smaller the in-plane phase difference Re, the more optically isotropic the (meth)acrylic resin film 10 is, and the change in color tone can be suppressed when bonded to an optical device or used for optical inspection.
[0090] The haze value of the (meth)acrylic resin film 10 is preferably 1.0% or less. The lower the haze value, the less light scattering occurs when the (meth)acrylic resin film 10 is transmitted. For example, when the (meth)acrylic resin film 10 is incorporated into an optical device such as a display, light leakage due to scattered light can be suppressed.
[0091] The (meth)acrylic resin film 10 preferably contains an antioxidant to suppress changes in appearance such as yellowing. For example, it is preferred that the (meth)acrylic resin film 10 does not change in appearance even after being heated at 70° C. for 30 days.
[0092] One or more of a hard coat layer, an antistatic layer, an antireflection layer, an antifouling layer, an antiglare layer, a low refractive index layer, an adhesive layer, a release layer and the like may be laminated on one or both sides of the (meth)acrylic resin film 10 .
[0093] As the fluorine compound used in the composition for forming the low refractive index layer, there can be listed: fluorinated olefins, fluorinated vinyl ethers, fluorinated (meth) alkyl acrylates, etc., one or more polymers, i.e., fluorinated copolymers; condensates of silane compounds containing fluorinated alkyls, etc. The low refractive index layer can also be combined with a high refractive index layer to form an antireflection layer.
[0094] The (meth)acrylic resin film 10 has excellent adhesion between the first resin layer 11 and the second resin layer 12. For example, even when a cellophane tape adhesion test is performed (see the test method in Examples for details), only the cellophane tape peels off and the (meth)acrylic resin film 10 does not peel off from the polarizer.
[0095] The adhesive sheet of the embodiment is, for example, Figure 2 As shown in the figure, the adhesive layer 21 is formed on one side or both sides of the (meth) acrylic resin film 10. The adhesive layer 21 is preferably laminated on the second resin layer 12 side. When the adhesive layer 21 is formed on both sides of the (meth) acrylic resin film 10, the second resin layer 12 can be laminated on both sides of the first resin layer 11.
[0096] As the adhesive layer 21, an adhesive layer formed of a (meth) acrylic adhesive is preferred. The method of forming the adhesive layer on the (meth) acrylic resin film can be carried out by a known method. Specifically, a known coating method such as reverse coating, comma coating, gravure coating, slot die coating, Meyer rod coating, air knife coating, etc. can be used.
[0097] The adhesive sheet 20 may have a release film (not shown) to protect the adhesive surface of the adhesive layer 21. The surface of the release film opposite to the adhesive surface of the adhesive layer 21 may be subjected to a release treatment using a silicone or fluorine-based release agent.
[0098] The adhesive sheet 20 can be an optical film with an adhesive layer, in which an adhesive layer 21 is laminated on at least one side of an optical film formed by using a (meth) acrylic resin film 10 as a substrate. The adhesive sheet 20 can be a surface protection film bonded via the adhesive layer 21 in order to protect the surface of an adherend such as glass, an optical film, or an optical member.
[0099] The polarizing film of the embodiment is, for example, Figure 3 As shown in FIG. 1 , a (meth) acrylic resin film 10 is formed on one or both sides of the polarizer 31. The total thickness of the polarizing film 30 is preferably 80 μm or less. The polarizer 31 is not particularly limited, and examples thereof include a film containing iodine molecules (I 2 ) of the polyvinyl alcohol (PVA) layer.
[0100] The surface treatment applied to the protective layer of the polarizer 31 may be any of untreated, AG treated, LR treated, AR treated, AG-LR treated, and AG-AR treated, or a combination of these. Here, AG means anti-glare, LR means low reflection, and AR means anti-reflection.
[0101] The (meth) acrylic resin film 10 can be used as a protective layer on at least one side of the polarizer 31. Although not particularly shown in the figure, when the (meth) acrylic resin film 10 of the embodiment is used on one side of the polarizer 31, another protective layer may be used on the opposite side. Examples of the other protective layer include acrylic resins such as triacetyl cellulose (TAC) and polymethyl methacrylate (PMMA), polyester resins such as polyethylene terephthalate (PET), cyclic olefin polymers, and polycarbonates.
[0102] Example
[0103] Hereinafter, the present invention will be specifically described with reference to examples.
[0104] <Production of the first (meth)acrylic resin composition>
[0105] Nitrogen was introduced into a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet pipe, and the air in the reaction apparatus was replaced with nitrogen. Then, the monomers shown in (A) of Table 1 were added to the reaction apparatus so that the total amount of (A-1) was 100 parts by weight, and a solvent (ethyl acetate) was added. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was added dropwise, and the mixture was heated to 65° C. and reacted for a predetermined time to obtain a first (meth)acrylic polymer solution. To the first (meth)acrylic polymer solution, the rubber compound shown in Table 1 and the additives shown in (A-3) and (A-4) were added, and the mixture was stirred and mixed to obtain a first (meth)acrylic resin composition.
[0106] The weight average molecular weight (Mw) of (A) was measured at the stage of the first (meth)acrylic polymer solution. In Comparative Example 10, a commercially available PMMA film (thickness 80 μm) produced by melt extrusion was used, so the film was dissolved in methyl ethyl ketone (MEK) solvent to measure the Mw of the polymer.
[0107]
Table 1
[0108]
[0109] The meanings of the abbreviations used in Table 1 (compound names, etc.) are as follows. In Table 1, the numerical values following these abbreviations are parts by weight relative to 100 parts by weight of the total of (A-1).
[0110] As (A-1), methyl methacrylate (MMA), methyl acrylate (MA), n-butyl methacrylate (BMA), ethyl methacrylate (EMA), tert-butyl acrylate (TBA), and isobutyl methacrylate (IBMA) were used.
[0111] As (A-2), 8-hydroxyoctyl methacrylate (8HOMA), 6-hydroxyhexyl methacrylate (6HHMA), 4-hydroxybutyl methacrylate (4HBMA), 2-hydroxyethyl methacrylate (HEMA), acrylic acid (Aac), 8-hydroxyoctyl acrylate (8HOA), and 6-hydroxyhexyl acrylate (6HHA) were used.
[0112] As the rubber compound (particle size is a volume-based average particle size), "M-230" is KANE ACE (registered trademark) M-230 (core-shell particles, particle size: 0.1 μm, core: SBR, shell: MMA, a trade name of Kaneka Corporation), "M-210" is KANE ACE (registered trademark) M-210 (core-shell particles, particle size: 0.2 μm, core: SBR, shell: MMA, a trade name of Kaneka Corporation), "B-513" is KANE ACE (registered trademark) B-513 (core-shell particles, particle size: 0.2 μm, core: butadiene, shell: MMA, a trade name of Kaneka Corporation), and "LP-4100" is Metablen (registered trademark) LP-4100 (acrylic rubber particles, particle size: 1 μm, a trade name of Mitsubishi Chemical Corporation).
[0113] As (A-3), "HX" is Coronate (registered trademark) HX (HDI isocyanurate, trade name of Tosoh Corporation), "HL" is Coronate (registered trademark) HL (HDI adduct, trade name of Tosoh Corporation), "140N" is Takenate (registered trademark) D-140N (IPDI adduct, trade name of Mitsui Chemicals, Inc.), and "TX" is TETRAD (registered trademark)-X (tetrafunctional epoxy compound, trade name of Mitsubishi Gas Chemical Corporation).
[0114] As (A-4), "C-1" is Irganox (registered trademark) 1010 (phenolic antioxidant, trade name of BASF), "C-2" is Tinuvin (registered trademark) 292 (hindered amine antioxidant, trade name of BASF), "C-3" is Irgafos (registered trademark) 168 (phosphite antioxidant, trade name of BASF), and "C-4" is Irganox (registered trademark) PS802FL (thioether antioxidant, trade name of BASF).
[0115] <Production of Second (Meth)Acrylic Resin Composition>
[0116] Nitrogen was introduced into a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet pipe, and the air in the reaction apparatus was replaced with nitrogen. Then, the monomers shown in (B) of Table 2 were added to the reaction apparatus so that the total amount of (B-1) was 100 parts by weight, and a solvent (ethyl acetate) was added. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was added dropwise, heated to 65° C., and reacted for a predetermined time to obtain a second (meth) acrylic polymer solution. To the second (meth) acrylic polymer solution, the rubber compound shown in Table 2 and the additives shown in (B-3) and (B-4) were added, and stirred and mixed to obtain a second (meth) acrylic resin composition.
[0117] The weight average molecular weight (Mw) of (B) was measured in the step of preparing the second (meth)acrylic polymer solution. In Comparative Examples 1 and 9, the second resin layer was not laminated.
[0118]
Table 2
[0119]
[0120] The meanings of the abbreviations used in Table 2 (compound names, etc.) are as follows. In Table 2, the numerical values following these abbreviations are parts by weight relative to 100 parts by weight of the total of (B-1).
[0121] As (B-1), methyl methacrylate (MMA), 2-ethylhexyl acrylate (2EHA), n-butyl acrylate (BA), ethyl acrylate (EA), isooctyl acrylate (IOA), and methyl acrylate (MA) were used.
[0122] As (B-2), 8-hydroxyoctyl acrylate (8HOA), 6-hydroxyhexyl acrylate (6HHA), 4-hydroxybutyl acrylate (4HBA), 2-hydroxyethyl acrylate (HEA), acrylic acid (Aac), and 2-hydroxyethyl methacrylate (2HEMA) were used.
[0123] The rubber compounds in Table 2 and (B-4) use the same abbreviations as the rubber compounds in Table 1 and (A-4). In (B-3), "HX", "HL", and "TX" use the same abbreviations as in Table 1. "TPA-100" is Duranate (registered trademark) TPA-100 (HDI isocyanurate, a trade name of Asahi Kasei Corporation). "B-3-1" is a bifunctional isocyanate compound obtained by reacting HDI with 2,2-dimethyl-1,3-propanediol monohydroxypivalate. "B-3-2" is a bifunctional isocyanate compound obtained by reacting HDI with 1,6-hexanediol.
[0124] <Production of (meth)acrylic resin film>
[0125] In Examples 1 to 5 and Comparative Examples 1 to 9, the (meth) acrylic resin compositions shown in Tables 1 to 2 were made into resin films by solution casting, and were dried and cross-linked under temperature conditions suitable for solvent drying and cross-linking agent curing, and then laminated. The thickness of the first resin layer is shown in Table 1, and the thickness of the second resin layer is shown in Table 2. In Comparative Example 10, the commercially available PMMA film described above was used. In the description of the test method shown below, the (meth) acrylic resin film of the Example or Comparative Example is referred to as a test film.
[0126] <Adhesion test>
[0127] The surface of the test film on the side where the polarizer is attached was subjected to corona treatment (0.15 kW, 3 m / min) and adhered to the PVA layer of the polarizing plate via a PVA adhesive. The polarizing plate has a 30 μm PVA layer on the polarizer and a 30 μm TAC substrate on the opposite side. As the PVA adhesive, a compound made by Mitsubishi Chemical (100 parts of GOHSENX (registered trademark) Z-200 and 10 parts of Safelink (registered trademark) SPM-01) was applied.
[0128] The test film was attached to a polarizing plate and dried at 80°C for 5 minutes, then taken out of the oven and left at 23°C for 1 hour, and then a cellophane tape was attached to the surface of the test film. The cellophane tape was peeled off at a speed of 300 mm / min in a 180° direction, and the state of the test film was visually determined.
[0129] Adhesion was evaluated as follows: "○" when only the cellophane tape peeled off, "△" when the test film peeled off with part of the test film remaining on the peeled cellophane tape, and "×" when the test film remained entirely on the cellophane tape and peeled off.
[0130] <Total thickness of polarizing plate>
[0131] A polarizing plate was prepared using a test film as a substrate on one surface, a PVA layer of 30 μm as a polarizer, and a TAC layer of 30 μm as a substrate on the other side, and the total thickness of the polarizing plate was measured.
[0132] <Haze value>
[0133] The total haze value of the test film was measured using a haze meter (Murakami Color Laboratory Co., Ltd., model: HM-150N) in accordance with JIS K7136 (2000).
[0134] <Appearance Changes>
[0135] After the test piece made from the test film was placed at 70°C for 30 days, the change in appearance of the test piece was visually judged. The appearance of the test piece was compared with the appearance of the test film before being placed at 70°C for 30 days (or a test film that can be assumed to have no change in appearance after being placed at 23°C for the same period of time), and the case where there was no change in appearance was evaluated as "○", the case where there was a partial change in color tone of the appearance was evaluated as "△", and the case where there was a change in appearance and yellowing was evaluated as "×".
[0136] <Folding resistance>
[0137] Using a test piece prepared from the test film, the number of reciprocating bends (folding endurance) until the test piece breaks was measured in accordance with JIS P8115.
[0138] <Solvent resistance>
[0139] The mass of the test piece made from the test film was accurately measured, and after being immersed in methyl ethyl ketone (MEK) for 24 hours, it was filtered through a 200-mesh metal mesh. The filtrate was dried at 100°C for 1 hour, and the mass of the obtained insoluble component (residue) was accurately measured to determine the gel fraction (%).
[0140] Gel fraction (%) = mass of insoluble components (g) / mass of test piece (g) × 100
[0141] <Tensile strength and elongation at break>
[0142] A shear tensile test was carried out using a test piece prepared from the test film to determine the values of tensile breaking strength (MPa) and breaking elongation (%).
[0143] <Phase difference Re>
[0144] Using a test piece prepared from the test film, the value (nm) of the in-plane retardation (Re) was measured using a retardation measuring device.
[0145]
Table 3
[0146]
[0147] As shown in Table 3, the (meth)acrylic resin films of Examples 1 to 5 are excellent in folding resistance, cut resistance, elongation, and solvent resistance, and can improve adhesion to the adherend while maintaining the optical properties. The (meth)acrylic resin films of Comparative Examples 1 to 10 are inferior in any of folding resistance, cut resistance, elongation, solvent resistance, optical properties, and adhesion to the adherend.
Claims
1. A (meth)acrylic resin film, comprising a first resin layer and a second resin layer laminated together, The first resin layer is formed by cross-linking a first (meth)acrylic resin composition containing (A) a first (meth)acrylic polymer, a rubber compound, (A-3) a first cross-linking agent, and (A-4) a first antioxidant. The second resin layer is formed by crosslinking a second (meth)acrylic resin composition containing (B) a second (meth)acrylic polymer, (B-3) a second crosslinking agent, and (B-4) a second antioxidant, and serves as an adhesion-enhancing resin layer of the first resin layer, characterized in that: The (A) first (meth)acrylic polymer includes a copolymer having a weight average molecular weight of more than 100,000 and 1,000,000 or less, which is obtained by copolymerizing (A-1) a first (meth)acrylic acid alkyl ester and (A-2) a first copolymerizable monomer. In the first (meth)acrylic acid alkyl ester (A-1), 80 parts by weight or more of methyl methacrylate and one or more (meth)acrylic acid alkyl esters other than the methyl methacrylate whose homopolymer has a Tg of 0° C. or higher and whose alkyl group has carbon atoms of C1 to C14 are added together to make 100 parts by weight, In the (A-2) first copolymerizable monomer, the total amount of one or more copolymerizable monomers having a functional group capable of reacting with the (A-3) first crosslinking agent is 1.0 to 20.0 parts by weight, The content of the rubber compound is 1.0 to 25.0 parts by weight based on 100 parts by weight of the total of the (A-1) first alkyl (meth)acrylate. The (B) second (meth)acrylic polymer comprises a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000, which is obtained by copolymerizing (B-1) a second (meth)acrylic acid alkyl ester and (B-2) a second copolymerizable monomer. In the second (meth)acrylic acid alkyl ester (B-1), 80 parts by weight or more of methyl methacrylate and one or more (meth)acrylic acid alkyl esters other than the methyl methacrylate whose homopolymer Tg is 0° C. or less and whose alkyl group has carbon atoms of C2 to C18 are added together to 100 parts by weight, In the (B-2) second copolymerizable monomer, the total amount of one or more copolymerizable monomers containing no carboxyl group and containing a hydroxyl group is 5 to 30 parts by weight, The (B-3) second crosslinking agent is a difunctional or higher functional isocyanate compound, The content of the second crosslinking agent (B-3) is 1 to 5 parts by weight based on 100 parts by weight of the second alkyl (meth)acrylate (B-1). The thickness of the first resin layer is 10 μm or less, the thickness of the second resin layer is 5 μm or less, and the haze value of the (meth)acrylic resin film is 1.0% or less.
2. The (meth)acrylic resin film according to claim 1, characterized in that The (A-2) first copolymerizable monomer is one or more monomers selected from the group consisting of copolymerizable monomers containing a hydroxyl group and copolymerizable monomers containing a carboxyl group, The (A-3) first crosslinking agent is one or more selected from the group consisting of epoxy compounds, aziridine compounds and isocyanate compounds, The content of the first crosslinking agent (A-3) is 0.1 to 5 parts by weight based on 100 parts by weight of the first alkyl (meth)acrylate (A-1). The (A-4) first antioxidant is one or more selected from phenolic antioxidants, thioether antioxidants, phosphite antioxidants, and hindered amine antioxidants. The content of the first antioxidant (A-4) is 0.01 to 0.5 parts by weight based on 100 parts by weight of the first alkyl (meth)acrylate (A-1).
3. The (meth)acrylic resin film according to claim 1, characterized in that: The rubber compound is a core-shell particle formed of a rubber layer mainly composed of SBR or butadiene as a core part and an acrylic layer mainly composed of methyl methacrylate as a shell part. The volume-based average particle size of the core-shell particles is 0.1 μm to 0.3 μm.
4. The (meth)acrylic resin film according to claim 1, characterized in that: The (A-2) first copolymerizable monomer is a copolymerizable monomer containing a hydroxyl group, and the copolymerizable monomer containing a hydroxyl group is one or more selected from 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl methacrylate, 4-hydroxybutyl methacrylate, and 2-hydroxyethyl methacrylate.
5. The (meth)acrylic resin film according to claim 1, characterized in that: The (B-4) second antioxidant is one or more selected from phenolic antioxidants, thioether antioxidants, phosphite antioxidants, and hindered amine antioxidants. The content of the second antioxidant (B-4) is 0.01 to 0.5 parts by weight based on 100 parts by weight of the second alkyl (meth)acrylate (B-1).
6. The (meth)acrylic resin film according to claim 1, characterized in that: The (B-2) second copolymerizable monomer is a copolymerizable monomer containing a hydroxyl group, and the copolymerizable monomer containing a hydroxyl group is one or more selected from 8-hydroxyoctyl acrylate, 6-hydroxyhexyl acrylate, 4-hydroxybutyl acrylate, and 2-hydroxyethyl acrylate.
7. The (meth)acrylic resin film according to claim 1, characterized in that: The thickness of the first resin layer is 0.1 μm to 9 μm, and the thickness of the second resin layer is 0.1 μm to 5 μm.
8. The (meth)acrylic resin film according to claim 1, characterized in that: The (meth)acrylic resin film has an in-plane retardation Re of 1.0 nm or less.
9. The (meth)acrylic resin film according to claim 1, characterized in that: The (meth)acrylic resin film has a gel fraction of 90% or more as solvent resistance, a folding endurance of 200 times or more as measured in accordance with JIS P8115, and a breaking elongation of 20% or more as elongation.
10. The (meth)acrylic resin film according to claim 1, characterized in that: In a cellophane tape adhesion test in which the (meth)acrylic resin film was bonded to one side of a polarizer with a PVA adhesive, a cellophane tape was bonded to the surface of the (meth)acrylic resin film, and then peeled off, the (meth)acrylic resin film was not peeled off and only the cellophane tape was peeled off.
11. An adhesive sheet, characterized in that: The (meth)acrylic resin film according to any one of claims 1 to 10 has an adhesive layer formed on one or both surfaces thereof.
12. A polarizing film, characterized in that: The (meth)acrylic resin film according to any one of claims 1 to 10 is formed on one or both surfaces of a polarizer, wherein the total thickness of the polarizing film is 80 μm or less.
Citation Information
Cited By
Optical film composition, polarizer and display device
CN121086437A